Dietary methionine availability affects the main factors involved in muscle protein turnover in rainbow trout (Oncorhynchus mykiss). Issue 4 (30th May 2014) - Belghit, Ikram; Skiba-Cassy, Sandrine; Geurden, Inge; Dias, Karine; Surget, Anne; Kaushik, Sadasivam; Panserat, Stéphane; Seiliez, Iban
Abstract : Methionine is a limiting essential amino acid in most plant-based ingredients of fish feed. In the present study, we aimed to determine the effect of dietary methionine concentrations on several main factors involved in the regulation of mRNA translation and the two major proteolytic pathways (ubiquitin–proteasome and autophagy-lysosomal) in the white muscle of rainbow trout ( Oncorhynchus mykiss ). The fish were fed for 6 weeks one of the three isonitrogenous diets providing three different methionine concentrations (deficient (DEF), adequate (ADQ) and excess (EXC)). At the end of the experiment, the fish fed the DEF diet had a significantly lower body weight and feed efficiency compared with those fed the EXC and ADQ diets. This reduction in the growth of fish fed the DEF diet was accompanied by a decrease in the activation of the translation initiation factors ribosomal protein S6 and eIF2α. The levels of the main autophagy-related markers (LC3-II and beclin 1) as well as the expression of several autophagy genes ( atg4b, atg12 l, Uvrag, SQSTM1, Mul1 and Bnip3 ) were higher in the white muscle of fish fed the DEF diet. Similarly, the mRNA levels of several proteasome-related genes ( Fbx32, MuRF2, MuRF3, ZNF216 and Trim32 ) were significantly up-regulated by methionine limitation. Together, these results extend our understanding of mechanisms regulating the reduction of muscle growth induced by dietary methionine deficiency, providing valuable information on the biomarkers of the effects of low-fishmeal diets.